Faculty Development Practices in Canadian Universities - Konrad, Abram G. (Canadian Journal of Higher Education, 1983)
This article reports on a survey of faculty development practices in Canadian universities - the extent of their use and estimated effectiveness. Sixty percent of the universities had an organized program, although only 40 percent had a coordinator of development practices. Traditional practices, like sabbaticals, travel funds, and newsletters, were most common, although some of the least used practices were judged most effective. The most pressing faculty development needs were in instructional improvement, rather than in personal or organizational development. Participation in development activities was greatest among good teachers who wanted to get better, rather than among those who really needed to improve. For development programs to become more effective, it seems that institutional commitments for faculty development will have to be strengthened, both organizationally and financially.